2017
DOI: 10.5599/jese.458
|View full text |Cite
|
Sign up to set email alerts
|

Graphene-modified nickel foam electrode for cathodic degradation of nitrofuranzone: Kinetics, transformation products and toxicity

Abstract: Simple, efficient, and durable electrodes are highly demanded for practical electrochemical process. In this study, a reduced graphene oxide modified nickel foam electrode (GR-Ni foam)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Studies have shown that conventional WWTPs are inefficient in removing the wide variety of antimicrobial residues in wastewater and may convert them into other chemical forms (treatment TPs). Remaining residues and treatment TPs are released together to the aquatic environment via effluent discharge. , Conventional biological treatments, additional treatment steps such as removal by adsorption and filtration, , and several more advanced treatment techniques (e.g., advanced oxidation, reverse osmosis, or electrochemical degradation ) have been investigated, but complete removal of the entire suite of antimicrobial classes by one single treatment method remains challenging. Owing to inefficient treatment methods and the fact that 44% of domestic wastewater is still not safely treated globally, many studies have reported the presence of antimicrobial parent compounds and related TPs in aquatic environments worldwide. As the COVID-19 pandemic only slowly recedes, the occurrence of antivirals used for treating COVID-19 and their TPs in water is also expected …”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that conventional WWTPs are inefficient in removing the wide variety of antimicrobial residues in wastewater and may convert them into other chemical forms (treatment TPs). Remaining residues and treatment TPs are released together to the aquatic environment via effluent discharge. , Conventional biological treatments, additional treatment steps such as removal by adsorption and filtration, , and several more advanced treatment techniques (e.g., advanced oxidation, reverse osmosis, or electrochemical degradation ) have been investigated, but complete removal of the entire suite of antimicrobial classes by one single treatment method remains challenging. Owing to inefficient treatment methods and the fact that 44% of domestic wastewater is still not safely treated globally, many studies have reported the presence of antimicrobial parent compounds and related TPs in aquatic environments worldwide. As the COVID-19 pandemic only slowly recedes, the occurrence of antivirals used for treating COVID-19 and their TPs in water is also expected …”
Section: Introductionmentioning
confidence: 99%
“…Graphene (Gr) nano sheets have a great potential for the applications in the development of electrochemical sensors and biosensors. Gr is used as a support material to improve the electrochemical reactivity of molecules on the surface of modified electrode, what is due to its superior mechanical, electrical, thermal, and optical properties [32]. On the other side, its low energy storage capacity greatly hinders its extensive use.…”
Section: Introductionmentioning
confidence: 99%